CREATING A COLLABORATIVE ADMINISTRATIVE NETWORK MODEL WITH MANY SECTORS IN CARRYING OUT THE MISSION OF PHETCHABURI BUDDHIST COLLEGE - Decha, Puangngam; Songkram, Samnavathana Rtn (Journal of MCU Phetchaburi Review, 2025)
This research aimed to: 1) study the missions of Phetchaburi Buddhist College and its network partners; 2) study the process of building collaboration with network partners in Phetchaburi Province; and 3) propose a collaborative networking model for the development of Phetchaburi Buddhist College. The research utilized qualitative methods, involving 17 monks or individuals, and action research, involving 15 monks or individuals. The findings revealed that Phetchaburi Buddhist College's mission is to integrate Buddhist education with modern sciences to develop the mind and society, and to serve as an international center for Buddhism. Phetchaburi Province's mission is to administer public administration and develop quality of life, which aligns with the college's role in fostering morality and local development. The collaborative networking process begins with identifying shared problems, engaging in dialogue to foster understanding, delegating clear missions, fostering trust, and jointly resolving issues using the AAR (Action Review) method. An appropriate collaborative network model should feature collaborative structures, shared decision-making, clear rules, and transparent management, with leaders acting as advocates, supporters, and articulate stakeholders. The success of network management depends on shared goals, trust, effective communication, conflict management, flexibility, strong leadership, and a monitoring and evaluation system to ensure sustainable collaboration that benefits society as a whole.